Outsourcing Sumberdaya Manusia: Tinjauan dari Perspektif Vendor dan Karyawan - Salamah Wahyuni; M.S. Idrus; Djumilah Zain; Mintarti Rahayu (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
This research explores in depth the benefits and the risks of human resource outsourcing strategy from vendor and employee perspective’s. The qualitative approach was used because this research is related to reasons and process of the benefit and the risk emergence for vendor and employee. The analysis unit consisted of the individual (the employee) and the organisation (the vendor company). The sources of data came from the informant, both the key and the second informant and the documents required. The determination of the informant was carried out by the purposive and snowball method. The data collection used the comprehensive interview method. The research findings revealed that: (1) the trust is the key point to achieve the benefit of human resources outsourcing for vendor in order to gain the opportunity to become the new player in the business, expands her/his business, and able to compete; (2) the risk for vendor has possitive correlation with skill and educations’ segment of the employee, the higher the skill/education, the higher the risk; (3) the new employee is more benefited of the outsourcing system compare to the old employee; (4) however, the old employee absorbed more of the risk of the outsourcing system compare to the new employee. Hence, this research proposes the human resources outsourcing model as a solution. This model focus on professionalism along with ethics and moral as a partnership and long term oriented. As a result, the model will be a mutually beneficial for both parties.Keywords: outsourcing, vendor, and employee